Access to Carbonyl Azides via Iodine(III)-Mediated Cross-Coupling - Qing Yan; Lanlan Lv; Li Xu; Stepanova E. V. Elena Vladimirovna; Alvey G. R. Gregory; Shatskiy A. Andrey; Kärkäs M. D. Markus; Xiang-Shan Wang (2024, 2024)
Title screen